2009
DOI: 10.1194/jlr.m800427-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Defective CFTR increases synthesis and mass of sphingolipids that modulate membrane composition and lipid signaling

Abstract: Cystic fibrosis (CF) is caused by mutations in the CF transmembrane conductance regulator (CFTR) that affect protein structure and channel function. CFTR, localized in the apical membrane within cholesterol and sphingomyelin rich regions, is an ABC transporter that functions as a chloride channel. Here, we report that expression of defective CFTR (#F508CFTR or decreased CFTR) in human lung epithelial cell lines increases sphingolipid synthesis and mass of sphinganine, sphingosine, four long-chain saturated cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 36 publications
3
43
0
Order By: Relevance
“…aSMase was the first SMase to be shown to have a role in a disease (47), as types A and B Niemann-Pick disease result from the deficient activity of aSMase. Recent reports point toward aSMase as the target responsible for ceramide generation in various pathologies (6,9,10,23). Although a role for the lysosomal aSMase has been described in edema (48), and also suggested to play a role in other pulmonary pathologies, such as cystic fibrosis (9,49) and emphysema (5), our data suggest that it is nSMase2 that serves as an exclusive target to generate ceramide under the stress of CS exposure.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…aSMase was the first SMase to be shown to have a role in a disease (47), as types A and B Niemann-Pick disease result from the deficient activity of aSMase. Recent reports point toward aSMase as the target responsible for ceramide generation in various pathologies (6,9,10,23). Although a role for the lysosomal aSMase has been described in edema (48), and also suggested to play a role in other pulmonary pathologies, such as cystic fibrosis (9,49) and emphysema (5), our data suggest that it is nSMase2 that serves as an exclusive target to generate ceramide under the stress of CS exposure.…”
Section: Discussionmentioning
confidence: 47%
“…Another study, based again on the protective effects of fumonisin B1 in a guinea pig asthma model, also proposed a role for increased ceramide-mediated oxidative stress in the pathogenesis of asthma (8). Teichgraber and colleagues (9) and Hamai and colleagues (10) have recently reported that ceramide accumulation mediates inflammation, cell death, and infection susceptibility in cystic fibrosis.…”
mentioning
confidence: 99%
“…CFTR is involved in the cellular uptake of S1P (52), and sphingolipid synthesis is increased in CF epithelial cells (20). It is tempting to speculate that CFTR could be involved in the secretion of S1P, which would explain the lower concentrations in BALF despite increased de novo sphingolipid synthesis.…”
Section: Discussionmentioning
confidence: 90%
“…The culture of CF DCs in bronchoalveolar lavage fluid (BALF) from wild-type (WT) mice improved their activation and maturation, suggesting that factors in the pulmonary milieu contribute to the CF DC phenotype. Based on our previous observations that CFTR dysfunction causes abnormalities in sphingolipid metabolism (20), we found that sphingosine-1-phosphate (S1P), a critical mediator for immune cell trafficking and DC activation (21)(22)(23), decreased in CF BALF. We demonstrate that CF BALF supplemented with S1P normalizes the maturation of CF DCs.…”
mentioning
confidence: 99%
“…In a previous study (36), it was reported that both Esc(1-21) and its diastereomer, Esc(1-21)-1c, are not toxic to A549 epithelial cells up to 64 M, and that the diastereomer is substantially less toxic when used at higher concentrations (36). Although A549 cells possess morphological and biochemical properties of alveolar epithelial cells (type II pneumocytes) (17), they do not express CFTR (43,44). Therefore, we studied the effect of both esculentin peptides on the viability of airway epithelial cells stably expressing the most common CFTR mutation (⌬F508) After overnight incubation at 37°C in a 5% CO 2 atmosphere, the medium was replaced with 100 l fresh MEMg supplemented with the peptides at different concentrations.…”
Section: Resultsmentioning
confidence: 99%